2017
DOI: 10.1021/acs.jmedchem.6b01720
|View full text |Cite
|
Sign up to set email alerts
|

Chromone as a Privileged Scaffold in Drug Discovery: Recent Advances

Abstract: The use of privileged structures in drug discovery has proven to be an effective strategy, allowing the generation of innovative hits/leads and successful optimization processes. Chromone is recognized as a privileged structure and a useful template for the design of novel compounds with potential pharmacological interest, particularly in the field of neurodegenerative, inflammatory, and infectious diseases as well as diabetes and cancer. This perspective provides the reader with an update of an earlier articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
179
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(180 citation statements)
references
References 139 publications
(226 reference statements)
0
179
0
1
Order By: Relevance
“…Procyanidins, the most abundant class of proanthocyanidins found in plants [88], show no cytotoxic effects on normal cells [90], although they are able to inhibit cell proliferation and induce apoptotic death in cancer cells by increasing the ROS levels [91], decreasing the mitochondrial membrane potential and activating caspase-3 [92]. Chromones and their derivatives are heterocyclic compounds distributed throughout the plant kingdom [93] known for presenting various pharmacological activities, including antioxidant and anticancer activities, especially against multiple drug-resistant tumor cell lines [94,95]. …”
Section: Discussionmentioning
confidence: 99%
“…Procyanidins, the most abundant class of proanthocyanidins found in plants [88], show no cytotoxic effects on normal cells [90], although they are able to inhibit cell proliferation and induce apoptotic death in cancer cells by increasing the ROS levels [91], decreasing the mitochondrial membrane potential and activating caspase-3 [92]. Chromones and their derivatives are heterocyclic compounds distributed throughout the plant kingdom [93] known for presenting various pharmacological activities, including antioxidant and anticancer activities, especially against multiple drug-resistant tumor cell lines [94,95]. …”
Section: Discussionmentioning
confidence: 99%
“…Chromone is recognized as a privileged structure and a useful template for the design of novel compounds with potential pharmacological interest, particularly in the field of neurodegenerative, inflammatory, and infectious diseases as well as diabetes and cancer (Reis, Gaspar, Milhazes, & Borges, ). The chromone moiety (1,4‐benzopyrone), shown in Figure , is the essential component of pharmacophores of a large number of bioactive molecules (Vanguru, Merugu, Garimella, & Laxminarayana, ).…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…Chromone is recognized as a privileged structure and a useful template for the design of novel compounds with potential pharmacological interest, particularly in the field of neurodegenerative, inflammatory, and infectious diseases as well as diabetes and cancer (Reis, Gaspar, Milhazes, & Borges, 2017). The chromone moiety…”
Section: Phenolic Acids-hydroxycinnamic and Hydroxybenzoic Acidsmentioning
confidence: 99%
“…Studies have identified various scaffolds or core structures that have privileged characteristics in terms of the activity of a certain target. 49,50,51 Core structure selection is the starting point in a scaffold-based drug discovery. Choosing or designing a proper initial scaffold is never trivial, and medicinal chemists may need enough experience to get such a skill.…”
Section: Core Selectionmentioning
confidence: 99%